2015
DOI: 10.21082/jpptp.v34n2.2015.p89-96
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Varietas Padi Menggunakan Pengolahan Citra Digital dan Analisis Diskriminan

Abstract: <p>Identification of the authenticity of variety is important in order to ensure the purly of rice variety. Variety identification based on visual traits is a common technique, but it is difficult to be applied when ones encounter almost similar varieties. An alternative technique is using the image processing analysis combined with the discriminant analysis. The research objectives were: (1) to develop the geometrical, shape and textural description of rice varieties (Ciherang, Inpari 10 and Inpari 13) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 6 publications
0
5
0
9
Order By: Relevance
“…Identifikasi varietas padi umumnya berdasarkan deskripsi secara visual, namun teknik tersebut sulit mengenali varietas yang mempunyai morfologi benih serupa (Adnan et al, 2015). Teknik yang berpotensi digunakan untuk identifikasi benih padi antara lain Simple Sequence Repeat (SSR) (Mulsanti et al, 2013), khusus untuk membedakan tetua padi hibrida, varietas padi yang berbeda atau campuran varietas lain, bahkan pada benih yang tertular penyakit.…”
Section: Pendahuluanunclassified
“…Identifikasi varietas padi umumnya berdasarkan deskripsi secara visual, namun teknik tersebut sulit mengenali varietas yang mempunyai morfologi benih serupa (Adnan et al, 2015). Teknik yang berpotensi digunakan untuk identifikasi benih padi antara lain Simple Sequence Repeat (SSR) (Mulsanti et al, 2013), khusus untuk membedakan tetua padi hibrida, varietas padi yang berbeda atau campuran varietas lain, bahkan pada benih yang tertular penyakit.…”
Section: Pendahuluanunclassified
“…Kuo et al (2016) discriminated rice grain by quantifying morphological parameters, texture and color with an accuracy of 89.1%. Adnan et al (2015) stated that round parameter had a considerable coefficient compared to other parameters, therefore it influenced the mode classified for different rice varieties.…”
Section: Rice Seed Identificationmentioning
confidence: 99%
“…A few researchers have measured the morphology of rice seed. Adnan et al (2015) identified rice variety based on area, perimeter, minimum feret, aspect ratio and round and got an accurate value of more than 50%. Others researchers (Kuo et al 2016) obtained an accurate value of 89%.…”
Section: Seed Purity Clarification Using Gotmentioning
confidence: 99%
See 2 more Smart Citations